Molecular detection of blaOXA-10(OXA-10) type Beta-lactamase encoding gene among extended spectrum Beta-lactamase isolates of Pseudomonas aeruginosa - Aryan R. Ganjo; Isam Y. Mansoor (Zanco Journal of Medical Sciences, 2020)
Background and objective: Pseudomonas aeruginosa is an opportunistic pathogen and inherently resistant to many antibiotics and can mutate to even more resistant strains during therapy. Resistance to the antibiotics in this group of bacteria increased due to the activity of β-lactamase genes and one of the most important groups of genes, blaOXA gene producing enzymes. The current study aimed to determine the prevalence of Ambler class D β-lactamases, including OXA-10 gene among P. aeruginosa isolated from patients in Erbil, Kurdistan. Methods: Different clinical specimens were taken from patients with clinical symptoms of infection during one year. Identification was carried out on all isolates by Vitek2 system. Antibiotic susceptibility for antimicrobial agents was performed according to the clinical and laboratory standards institute (CLSI) guidelines. Production of Ambler class D β-lactamases was confirmed by polymerase chain reaction technique. Results: A total of 100 isolates of P. aeruginosa, 57 isolates (57%) had shown resistance to six or more than six antibiotics, and 15 isolates showed resistance to one antibiotic. Also, none of the resistant isolates were showed complete resistance to all antibiotics. Out of 89 P. aeruginosa, 38.2% of isolates possessed the blaOXA-10 gene. Conclusion: The results revealed the occurrence of extended-spectrum β- lactamases producing Pseudomonas aeruginous, and proper infection control practices are crucial to avert the spreading of ESBL-producing isolates in hospitals.